2017
DOI: 10.1159/000481354
|View full text |Cite
|
Sign up to set email alerts
|

Leser-Trélat Syndrome in a Male with Breast Carcinoma and Eyelid Basal Cell Carcinoma

Abstract: Purpose: Leser-Trélat syndrome consists of appearance of a solid tumor-like carcinoma breast, colon, or stomach following eruption of multiple seborrheic keratoses (SK) of the skin. We present an unusual and possibly the first case report of Leser-Trélat syndrome in a male patient with a history of mastectomy for breast carcinoma who presented to us with a second malignancy in the form of basal cell carcinoma (BCC) of the lower eyelid. Procedure: A 75-year-old male presented in 2014 with a history of modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…It has been observed that in many patients who show the Leser-Trélat sign, another paraneoplastic disease occurs at the same time, so that a careful examination and precise anamnesis cannot be assessed. [2][3][4][5][6][7] As epidermal growth factor (EGF) receptors are present on basal keratinocytes, it has been suggested that greater importance should be given to combining molecular characteristics of multiple SKs with immunohistochemical analyzes of EGFR proteins to determine the likelihood of Leser-Trélat syndrome and consequently a high risk of disease. 8 At the same time, it is suggested for EGFR immunohistochemical analysis to be limited, i.e, to indicate the presence of LTS only when some additional clinical manifestations are present, such as: acute morphological changes in long-standing multiple SK, sudden, multiple "eruption" of SK, association with acanthosis or other paraneoplastic manifestations of the skin, a younger age of the patient at the onset of SK, and malignancies in personal and/or family history.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that in many patients who show the Leser-Trélat sign, another paraneoplastic disease occurs at the same time, so that a careful examination and precise anamnesis cannot be assessed. [2][3][4][5][6][7] As epidermal growth factor (EGF) receptors are present on basal keratinocytes, it has been suggested that greater importance should be given to combining molecular characteristics of multiple SKs with immunohistochemical analyzes of EGFR proteins to determine the likelihood of Leser-Trélat syndrome and consequently a high risk of disease. 8 At the same time, it is suggested for EGFR immunohistochemical analysis to be limited, i.e, to indicate the presence of LTS only when some additional clinical manifestations are present, such as: acute morphological changes in long-standing multiple SK, sudden, multiple "eruption" of SK, association with acanthosis or other paraneoplastic manifestations of the skin, a younger age of the patient at the onset of SK, and malignancies in personal and/or family history.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of numerous seborrheic keratoses (especially if they are "eruptive", large and bizarre in shape [1][2][3][4][5][6][7] ), should raise suspicion of LT phenomenon, or internal malignancy in the patient, and result in relevant diagnostic procedures to detect possible latent malignancy. It would be wise for the doctors of all disciplines to be acquainted with the existence of the LT sign (syndrome) and the possible clinical implications of it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El tratamiento consiste en la identificación y el manejo de la neoplasia maligna subyacente, lo cual resuelve las queratosis seborreicas asociadas hasta en un 50% de los pacientes (1,10). La eliminación del resto de lesiones residuales y sintomáticas puede realizarse con diversos métodos físicos, como la crioterapia, el curetaje, la eliminación por afeitado y la electrodesecación.…”
Section: Tratamientounclassified